5′-Triphosphate siRNA targeting MDR1 reverses multi-drug resistance and activates RIG-I-induced immune-stimulatory and apoptotic effects against human myeloid leukaemia cells. (July 2017) - Li, Dengzhe; Gale, Robert Peter; Liu, Yanfeng; Lei, Baoxia; Wang, Yuan; Diao, Dongmei; Zhang, Mei
Highlights: A 5′-triphosphate modified MDR1 specific siRNA against leukemia cells was proposed. Mechanisms include immune activation, pro-apoptosis and reverse drug resistance. It can synergize with doxorubicin which also has immune induction effects. Abstract: Multi-drug resistance (MDR), immune suppression and decreased apoptosis are important causes of therapy-failure in leukaemia. Short interfering RNAs (siRNAs) down-regulate gene transcription, have sequence-independent immune-stimulatory effects and synergize with other anti-cancer therapies in some experimental models. We designed a siRNA targeting MDR1 with 5′-triphosphate ends (3p-siRNA-MDR1). Treatment of leukaemia cells with 3p-siRNA-MDR1 down-regulated MDR1 expression, reduced-drug resistance and induced immune and pro-apoptotic effects in drug-resistant HL-60/Adr and K562/Adr human leukaemia cell lines. We show mechanisms-of-action of these effects involve alterations in the anti-viral cytosolic retinoic acid-inducible protein-I (RIG-I; encoded by RIG-I or DDX58 ) mediated type-I interferon signal induction, interferon-gamma-inducible protein 10 (IP-10; encoded by IP10 or CXCL10 ) secretion, major histocompatibility complex-I expression (MHC-I) and caspase-mediated cell apoptosis. 3p-siRNA-MDR1 transfection also enhanced the anti-leukaemia efficacy of doxorubicin. These data suggest a possible synergistic role for 3p-siRNA-MDR1 in anti-leukaemia therapy.